The effect of spironolactone on cardiovascular function and markers of fibrosis in people at increased risk of developing heart failure: the heart 'OMics' in AGEing (HOMAGE) randomized clinical trial. (20th November 2020) - Cleland, John G F; Ferreira, João Pedro; Mariottoni, Beatrice; Pellicori, Pierpaolo; Cuthbert, Joe; Verdonschot, Job A J; Petutschnigg, Johannes; Ahmed, Fozia Z; Cosmi, Franco; Brunner La Rocca, Hans-Peter; Mamas, Mamas A; Clark, Andrew L; et al.
Abstract: Aims : To investigate the effects of spironolactone on fibrosis and cardiac function in people at increased risk of developing heart failure. Methods and results : Randomized, open-label, blinded-endpoint trial comparing spironolactone (50 mg/day) or control for up to 9 months in people with, or at high risk of, coronary disease and raised plasma B-type natriuretic peptides. The primary endpoint was the interaction between baseline serum galectin-3 and changes in serum procollagen type-III N-terminal pro-peptide (PIIINP) in participants assigned to spironolactone or control. Procollagen type-I C-terminal pro-peptide (PICP) and collagen type-1 C-terminal telopeptide (CITP), reflecting synthesis and degradation of type-I collagen, were also measured. In 527 participants (median age 73 years, 26% women), changes in PIIINP were similar for spironolactone and control [mean difference (mdiff): −0.15; 95% confidence interval (CI) −0.44 to 0.15 μg/L; P  = 0.32] but those receiving spironolactone had greater reductions in PICP (mdiff: −8.1; 95% CI −11.9 to −4.3 μg/L; P  < 0.0001) and PICP/CITP ratio (mdiff: −2.9; 95% CI −4.3 to −1.5; <0.0001). No interactions with serum galectin were observed. Systolic blood pressure (mdiff: −10; 95% CI −13 to −7 mmHg; P  < 0.0001), left atrial volume (mdiff: −1; 95% CI −2 to 0 mL/m 2 ; P  = 0.010), and NT-proBNP (mdiff: −57; 95% CI −81 to −33 ng/L; P  < 0.0001) were reduced in those assigned spironolactone. Conclusions : Galectin-3 did not identify greater reductions in serum concentrations of collagen biomarkers in response to spironolactone. However, spironolactone may influence type-I collagen metabolism. Whether spironolactone can delay or prevent progression to symptomatic heart failure should be investigated.